Faktor Risiko Penggunaan Kelambu Long Lasting Insectiside Nets terhadap Kejadian Malaria - Muhamad Abas; Marlin Mayling Jarona; Bruce Mehue (Journal of Pharmaceutical and Health Research, 2023)
The Annual Parasite Index (API) of the Genyem Health Center in 2021 is 117 per 1,000 population. This figure is very high when you look at the government's malaria control target towards malaria elimination in 2030. Papua is free of malaria (API=1/1,000). This survey study was conducted to observe the level of damage to the long lasting insecticide net (LLIN) used by 162 malaria sufferers to prevent the incidence of malaria. Each respondent has been given a mosquito net in 2021 and then each one LLIN mosquito net. The results of the evaluation of the condition of the level of damage to the stage I LLIN mosquito nets showed that the mosquito nets used by malaria patients were mostly damaged at the level of damage to size 1 (r=<1 cm) as many as 18 mosquito nets (11.1%). The other levels of damage were each size 2 (r=1-3 cm) with 8 mosquito nets (4.9%), the size of the damage size 3 (r=4-5 cm) with 5 mosquito nets (3.1%), the size of the damage size 4 (r=>5 cm) 3 mosquito nets (1.9%), 8 mosquito nets that were not found or missing (4.9%). The results of in-depth interviews found that the damaged LLIN mosquito nets were caused by rat bites, attracted by nails, damaged during washing, burned by respondents due to itching (skin sensitivity effect), and were converted to kill fruit ants on rambutan trees, used to catch fish. Several LLIN mosquito nets were not found or were lost because the respondent gave LLIN mosquito nets to other family members who live elsewhere.The distribution of LLIN mosquito nets that are distributed to the community to prevent the bite of the Anopheles malaria mosquito needs to be done by providing counseling on how to use and care for LLIN mosquito nets.